IMMUNOMODULATOR, GROWTH PERFORMANCE AND HEMATOLOGICAL PROFILES OF VIUSID VET SUPPLEMENTATION ON PIGLETS - Ardana, Ida Bagus Komang; Soma, I Gede; Subawa, Anak Agung Ngurah; Putra, Dewa Ketut Harya (BALI MEDICAL JOURNAL; Vol 4 No 3 (2015), 2015)
Background: Immunity system plays important roles in maintaining health status in human as well as in animals.This work aims to study the effect of supplementation of food supplement Viusid vet 90 on growth performance, morbidity and mortality rates, hematological profile, and on antibody titer which may indicate its possible role as an immunomodulator. Methods: Sixty (60) piglets were used as the experimental animals divided into 2 groups, namely group without Viusid supplementation as the control group and that with Viusid supplementation starting from 3 days of age until 13 days of age (10 days of treatment). The dose of supplementation in the feed was 5 cc of Viusid given twice a day. At day 7 of age, the piglets were vaccinated intramuscularly with Hog cholera vaccine and it repeated at day 14 of age. The animals were weighed at the beginning of the experiment and again at Day 15 and then at the end the experiment at Day 30. At 20 days of age all animals were bled using vacuum tube containing anticoagulant EDTA. Subsequently the bloods were examined for hematological profiles using Manual ABC VET Automated blood counter. Finally, at 30 days of age they were all bled again for the assessment of their antibody titer against Hog cholera following ELISA method. Results: supplementation of Viusid vet 90 to piglets improves performance by reducing morbidity and mortality rates. As hematological profile and differential leucocyt count did not showed any abnormality then it may concluded that supplementation of Viusid is effective and safe for piglets. Moreover, the percentage Plate Count (PC) value for Hog cholera was seropositive (54.69%) and significantly higher than control (41.32%) and this could indicate that Viusid vet 90 act as a strong immunmodulator.
Keywords: piglet, Performance, morbidity, mortality, hematological profile, immunomodulator